Fuzzy Simple Partially Ordered Γ- Semigroups - K.V.Naga Lakshmi, N.Srimannarayana, Srinivas Telikepalli, A. Gangadhara Rao, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, it is shown that and are respectively fuzzy left and fuzzy right ideals of S. S is a fuzzy left(right) simple po- Γ -semigroup ( ) . It is proved that for any semi group S “TFAE” (1) S is left(right) simple po- Γ -semigroup. (2) S is a fuzzy left(right)simple Γ-semigroup. The union of all proper fuzzy ideals of S is the only fuzzy maximal ideal of S ,where S is a PO -Γ-Semigroupwith 'e', unity.